Comparison of Breaststroke Swimming Skills Through The Use of Media in Class X Students of Sanata Karya Langgur High School - Bernadus Frans Rahawarin; Idris Moh. Latar; Mariana. D. Hukubun (Peneliti.net, 2023)
This study analyses the comparison of breaststroke swimming ability through the use of learning media, namely waist safety aids (Save Belt) with hand bouy in class X students of SMA Sanata Karya Langgur. The use of methods in this study is an experiment with a post-test only group design. The study population was class X students of SMA Sanata Karya Langgur who could not swim, from the total population obtained 30 female students. The sampling technique was purposive sampling, from 30 students then grouped into two groups with the same number of 15 students per group. The first group uses a save belt tool and the second group uses a hand bouy tool. The measuring instrument or instrument used for the performance of breaststroke swimming skills uses an assessment rubric. The results showed that the scores obtained by students who used the save belt tool were 79-93, while students who used the hand bouy tool received scores of 36-60. The results of the t-test analysis resulted in a t-count value of 10.71 with 28 degrees of freedom, and a t-table value of 2.048 at a significant level of 5%, so t-count> t-table (10.71> 2.048). The conclusion is that there is a comparison of breaststroke swimming skills through the use of media with save belt tools with hand bouy tools in class X students of SMA Sanata Karya Langgur there is a difference.